Information Systems Security : 11th International Conference, ICISS 2015, Kolkata, India, December 16-20, 2015. Proceedings - Jajoda, Sushil; Mazumdar, Chandan; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the 11th International Conference on Information Systems Security, ICISS 2015, held in Kolkata, India, in December 2015. The 24 revised full papers and 8 short papers presented together with 4 invited papers were carefully reviewed and selected from 133 submissions. The papers address the following topics: access control; attacks and mitigation; cloud security; crypto systems and protocols; information flow control; sensor networks and cognitive radio; and watermarking and steganography.
Access control -- Attacks and mitigation -- Cloud security -- Crypto systems and protocols -- Information flow control -- Sensor networks and cognitive radio -- Watermarking and steganography.
Keywords: Computer security; Data encryption (Computer science).; Computer Communication Networks; Computer software; Information Systems; Systems and Data Security; Cryptology; Computer Communication Networks; Algorithm Analysis and Problem Complexity; Management of Computing and Information Systems